Open Ni site coupled with SO42- functionality to prompt the radical interconversion of (OH)-O-center dot <-> SO4 center dot- exploited to decompose refractory pollutants - Choe, Yun Jeong; Kim, Ji-Su; Kim, Hyoungchul; Kim, Jongsik (Elsevier BV, 2020)
Exposing SO42- functionalities on Fe2O3 to an electric environment can produce supported SO4 center dot- species via radical interconversion of (OH)-O-center dot <-> SO4 center dot-, which can degrade aqueous contaminants (phenol). This methodology is unique, has substantial potential, yet, is underexplored regarding how to mechanistically account for or to further accelerate radical transfer of (OH)-O-center dot -> SO4 center dot-. Herein, NiO serves as a novel platform to accommodate SO42- functionalities, whereas the resulting SO42--modified NiO (NiO (S)) was kinetically evaluated or subjected to density functional theory (DFT) calculations to clarify the benefits of surface Ni delta+ (delta <= 2), SO42-, or (OH)-O-center dot -> SO4 center dot-. NiO (S) was verified to contain abundant surface-labile O, facilitate electron transfer, and thus could increase H2O2 productivity. The Lewis acidity of Ni delta+ active to cleave H2O2 was also improved by SO42-, as evidenced by in situ diffuse reflectance Infrared Fourier transform spectra and Bader charge calculations. This helped enhance (OH)-O-center dot productivity of NiO (S) over NiO, whose energetics were computed and validated that %OH production was directed by (OH)-O-center dot desorption from Ni delta+. Furthermore, electron paramagnetic resonance spectroscopy and DFT calculations also substantiated NiO (S) was energetically favorable toward radical transfer from (OH)-O-center dot to SO4 center dot-, in which Ni bound to SO42- was identified to spur the formation of supported SO4 center dot- via electron exchange with SO42-/(OH)-O-center dot. In conjunction with mechanistic elucidation using theoretical calculations, kinetic assessment of H2O2 scission and phenol decomposition runs under various electric potentials corroborated (OH)-O-center dot desorption was the rate-determining step of overall (OH)-O-center dot <-> SO4 center dot- pathway. Importantly, NiO (S) synthesized at 400 degrees C could enhance the efficiency, reusability, and stability in decomposing phenol over NiO/Fe2O3 functionalized with SO42- at 300, 500, or 600 degrees C.